2022
DOI: 10.1053/j.gastro.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medications on COVID-19 Outcomes in Inflammatory Bowel Disease: Analysis of More Than 6000 Patients From an International Registry

Abstract: Bowel Disease (SECURE-IBD) database, an international, collaborative database created to monitor COVID-19 outcomes in patients with inflammatory bowel disease (IBD), has previously reported that corticosteroids and mesalamine or sulfasalazine are associated with an increased risk of severe COVID-19 and tumor necrosis factor (TNF) antagonists do not impact risk. 1 A follow-up report observed that patients on combination therapy with TNF antagonists and thiopurines appeared to be at higher risk of severe COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 9 publications
0
75
0
9
Order By: Relevance
“…Moreover, a recent report from the Surveillance Epidemiology of Coronavirus Under Research Exclusion for IBD (SECURE-IBD) registry demonstrated that among patients with IBD on various forms of IBD-directed therapy, only those on systemic corticosteroid therapy appear to be at relatively greater risk of adverse COVID-19 outcomes. 24 Those who would most likely benefit from a fourth mRNA COVID-19 vaccine dose include solid organ transplant recipients, those on systemic corticosteroids at the time of vaccination, those on concomitant therapies associated with a lower COVID-19 vaccine response (mycophenolate or B cell–depleting therapies), those who have comorbidities associated with adverse COVID-19 outcomes, and potentially those who received their third dose roughly ≥6 months prior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent report from the Surveillance Epidemiology of Coronavirus Under Research Exclusion for IBD (SECURE-IBD) registry demonstrated that among patients with IBD on various forms of IBD-directed therapy, only those on systemic corticosteroid therapy appear to be at relatively greater risk of adverse COVID-19 outcomes. 24 Those who would most likely benefit from a fourth mRNA COVID-19 vaccine dose include solid organ transplant recipients, those on systemic corticosteroids at the time of vaccination, those on concomitant therapies associated with a lower COVID-19 vaccine response (mycophenolate or B cell–depleting therapies), those who have comorbidities associated with adverse COVID-19 outcomes, and potentially those who received their third dose roughly ≥6 months prior.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the pandemic, the Surveillance Epidemiology of Coronavirus Under Research Exclusion (SECURE-IBD) international registry has helped clinicians and patients better understand outcomes of COVID-19 in patients with IBD. Prior to registry closure in January 2022, 7038 cases of COVID-19 from 74 countries had been reported to determine the impact of IBD treatment regimens on outcomes of COVID-19, including hospitalisation and severe COVID-19, defined as a composite of intensive care unit (ICU) admission, mechanical ventilation and death 33–38. Throughout the pandemic, SECURE-IBD has been a hugely informative resource for the IBD community, however, there are significant limitations with how representative the cohort is, in part secondary to the physician-led opt in nature of the registry.…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 99%
“…Figure created with data from refs. 30 36 and using BioRender.com. 5-ASA, 5-aminosalicylic acid; IBD, inflammatory bowel disease; ICU, intensive care unit; JAK-inhibitor, Janus kinase inhibitor; RR, relative risk; TNF, tumour necrosis factor.…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The CLARITY IBD study recently reported attenuated serological responses in IBD patients treated with infliximab in comparison to vedolizumab 1 , with the effect greatest in those on infliximab/thiopurine combination therapy. Independently, the global SECURE-IBD registry highlighted that infliximab/thiopurine combination therapy, but not infliximab or vedolizumab monotherapies, was associated with more severe clinical outcomes upon SARS-CoV-2 infection 2,3 .…”
Section: Textmentioning
confidence: 99%